“Implementación Del Cercado Eléctrico Con Paneles Solares En La Cabaña De La Universidad Técnica De Cotopaxi Extensión La Maná”. - Silva Zamora, Bryan Hernan (2022)
Security in our homes or workplace is a priority, for them residential security implements smart technologies that guarantee constant vigilance and have the ability to give an immediate response when there is an infraction in our real estate. Although we know that most of the electronic devices in homes are designed to use the electric current provided by the energy companies, but said electric energy causes direct and indirect damage to the environment, destroying the ecosystem to install its generators, power lines, etc. In recent decades there has been talk of renewable energy or clean energy, which many years ago was something impossible for that time, but thanks to technological advances today we can change the world using the renewable resources that our planet provides us such as; wind power, tidal power and solar power. The cabin, a real estate property of the Technical University of Cotopaxi, La Maná extension, today does not have a security system, for which it is exposed to any crime. Due to this need, the technological proposal that aims to implement and design a residential electric fence, using solar energy through photovoltaic cells, is disclosed. The design of the electric fence includes the use of a commercial energizer that needs current from the power lines for its operation, and our photovoltaic system delivers DC current, for which it must be corrected with an inverter.